Characteristics of Urgut Free Economic Zone Activity in Investment Processes in the Country - Djurayeva Iroda Bakhrom Kizi (International Journal on Integrated Education, 2023)
In this article, the directions and boundaries set by the leadership of the Republic of Uzbekistan within the framework of the organization and activity of the economic region "Urgut" have been changed and analyzed. The author's recommendations for the further improvement of the "Urgut" economic free zone are elaborated in the article.